Who will organize information and who will manage it? : Education of Information Professionals at the University of Zagreb - Lasić-Lazić, Jadranka (Array, 2002)
The paper examines the existing and perceived conception of information professionals' education in the curriculum of the Department of Information Sciences at the University of Zagreb. In curriculum the Department has always been specific in the way it views the field of information science and embraces four different profiles of information professionals within its undergraduate and postgraduate programme. The paper also examines how different profiles have envisaged their role and realised their mission within the Department curriculum since its foundation. Also, it attempts to envisage how the joint curriculum of the Department of Information Science could be further developed in order to fit into the broader framework of information society, its knowledge organization, communication and management.